Osteoporosis risk assessment in primary dental care—The attitudes of Swedish dentists, patients and medical specialists. (5th February 2020) - Gullberg, Joanna; Lindh, Christina; Axtelius, Björn; Horner, Keith; Devlin, Hugh; Povlsen, Lene
Abstract: Objective: To explore and identify the attitudes of dentists, patients and medical specialists regarding implementation of osteoporosis risk assessment into Swedish primary dental care. Background: Osteoporosis is a major health problem leading to fragility fractures. As shown in academic‐based research, dental radiological examination can be used for osteoporosis risk assessment. A substantial number of patients undergo radiographic examinations in primary dental care each year, but little is known about implementation of osteoporosis risk assessment in this setting. Materials and methods: A qualitative research approach using focus group discussions and manifest content analysis was applied. Five focus groups with dentists and representatives from patient support groups and a single individual interview with one medical specialist were included in the sample. Results: From the manifest content analysis, three categories emerged: (a) barriers to change in practice, (b) benefits to change in practice, and (c) needs and requirements prior to change in practice. Most participants felt that there was insufficient knowledge of osteoporosis as well as a heavy existing workload. A concern was expressed about medical practitioners' willingness to take on responsibility for patients referred by dentists. Representatives from patient support groups highlighted a lack of knowledge about osteoporosis among both the general public and the medical professionals. Clear guidelines and improved communication channels between stakeholders would have to be established to ensure a smooth treatment path for patients. Conclusion: Despite interest in osteoporosis risk assessment in primary dental care, there are political, workflow and educational barriers that must be overcome for successful implementation.